White matter correlates of impulsive behavior in healthy individuals: A diffusion magnetic resonance imaging study - Fatemeh Rashidi; Mohammadamin Parsaei; Iman Kiani; Arash Sadri; Mohammad Hadi Aarabi; Seyed Reza Darijani; Yune Sang Lee; Hossein Sanjari Moghaddam (PCN Reports)
Abstract Aim To explore white matter (WM) tracts linked to impulsivity using the diffusion magnetic resonance imaging (DMRI) connectometry method. Methods We analyzed 218 healthy participants from the Leipzig Study for Mind‐Body‐Emotion Interactions database. Impulsivity correlations with DMRI‐derived WM changes were assessed using Urgency‐Premeditation‐Perseverance‐Sensation (UPPS) Impulsive Behavior Scale subscales: lack of perseverance (PE), lack of premeditation (PM), sensation seeking (SS), and negative urgency. DMRI data were processed using connectometry, adjusting for sex and age, to examine WM tract integrity via quantitative anisotropy (QA). Also, two additional interaction analyses were conducted to separately examine the interaction effect between WM QA, and sex and age in predicting impulsive behavior scores. The significance level in our statistical analyses was set at a false discovery rate (FDR) below 0.05. Results QA in the bilateral cerebellum and middle cerebellar peduncle showed a negative association with PE and PM severity (FDR = 0.0004). QA in the middle cerebellar peduncle, corpus callosum body, and forceps major demonstrated a positive association with SS (FDR = 0.0001). Conversely, QA in forceps minor had a positive association with PM (FDR = 0.004), and QA in forceps minor and bilateral cingulum showed a positive association with SS (FDR = 0.0005). Age and sex had no significant effects on the association between WM QA and UPPS subscale scores. Conclusion Impulsivity is linked to distinct WM integrity changes in various tracts, including the corpus callosum, cerebellum, and cingulum, offering insights into the pathophysiology of impulsivity and guiding future research.